PENERAPAN MEDIA GAMBAR SEBAGAI UPAYA MENINGKATKAN KOSENTRASI BELAJAR ANAK USIA DINI - Sahrul Salingkat; Tomi Bidjai; Firman Yalumani (Damhil Education Journal, 2022)
Early childhood education is education that is shown to preschool children with the aim that children can develop their potential from an early age so that they can develop naturally as children. Early childhood learning must be interesting, with the concept of playing meaningfully. A teacher is obliged to provide media or teaching aids as attractive as possible so that children are interested in participating in the learning process and children easily understand the activities to be carried out.teachers more often provide worksheets as learning media, even though media can be easily made by utilizing the surrounding environment, such as natural materials. who have not used the media properly and often use worksheets, causing the learning process to be unvaried so that students become bored and do not pay attention to what is conveyed by the teacher. Realities like this can affect the learning process, the enthusiasm and ability of children to concentrate on learning and stress on the teacher.This study aims to increase the concentration of Early Childhood Learning in Kindandal Nusantara Kindergarten, Liang District, Banggai Islands Regency through image media.This research uses Classroom Action Research (CAR) which consists of two cycles. Each cycle consists of four stages, namely: planning, implementation, observation (observation) and reflection. The research subjects were groups A and B in Kindandal Nusantara Kindergarten, Liang District, Banggai Islands Regency.Based on the analysis in cycle I and cycle II, the writer concludes that image media can improve the development of students' learning concentration. With image media, children can be confident and concentrate well with an increase of 85%.